Nursing diagnoses associated with the national policy for health promotion - Camila Maciel Diniz (Investigación y Educación en Enfermería, 2017)
Objective. To identify the relationships between nursing diagnoses proposed by NANDA-I taxonomy II and the priority themes (PT) of the National Policy for Health Promotion (PNPS in Portuguse). Methods. An integrative literature review was carried out in the Scopus, Cinahl and SciELO databases, using the descriptors: health promotion, food habits, traffic accidents, drugs abuse, environment and public health. The search considered scientific articles published between 2000 and 2016. Results. Twelve articles were selected to identify and explore nursing actions related to PT. It was identified that although the said taxonomy offers a Domain called Health promotion, there is a need to relate the diagnoses of other domains to include the health actions described in the aforementioned Policy. It was observed that there is an attention and concern of the nursing professionals to address topics such as the training of managers and the promotion of healthy eating. In relation to the priority themes promotion of safe mobility and sustainable development, no nursing diagnoses were identified due to the scarcity of diagnoses related to them in the mentioned taxonomy. Conclusion. Although the NANDA-I taxonomy presents a specific domain on health promotion, these are not sufficient to meet the needs of the priority themes proposed by PNPS.